Tugas Guru dalam Proses Pembelajaran - Hazmi, Nahdatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to find out the teacher's duties in learning. The research method that I use is a type of qualitative descriptive research. Qualitative descriptive research. The results of the study, the teacher's task in the learning process still looks like: the existence of teachers who have not fully carried out their teaching and educating duties as teachers and lack of implementation of supervision from the principal to teachers in assessing how to teach teachers and correct shortcomings of the way the teacher carries out his duty. Conclusions, factors that influence the lack of implementation of the teacher's duties in the learning process that comes from the teacher itself and from students. The factors that influence the teacher itself such as physical and mental inadequacies in the learning process and the level of teacher income that affect the teacher's lack of focus are disturbed because the teacher thinks about the income coming from outside and the unfavorable climate that can adversely affect into the learning process. Keywords: Teacher Assignment, Learning Process